Bordetella adenylate cyclase toxin interacts with filamentous haemagglutinin to inhibit biofilm formation in vitro. Issue 2 (3rd November 2016) - Hoffman, Casandra; Eby, Joshua; Gray, Mary; Heath Damron, F.; Melvin, Jeffrey; Cotter, Peggy; Hewlett, Erik
Summary: Bordetella pertussis, the causative agent of whooping cough, secretes and releases adenylate cyclase toxin (ACT), which is a protein bacterial toxin that targets host cells and disarms immune defenses. ACT binds filamentous haemagglutinin (FHA), a surface‐displayed adhesin, and until now, the consequences of this interaction were unknown. A B. bronchiseptica mutant lacking ACT produced more biofilm than the parental strain; leading Irie et al . to propose the ACT‐FHA interaction could be responsible for biofilm inhibition. Here we characterize the physical interaction of ACT with FHA and provide evidence linking that interaction to inhibition of biofilm in vitro . Exogenous ACT inhibits biofilm formation in a concentration‐dependent manner and the N‐terminal catalytic domain of ACT (AC domain) is necessary and sufficient for this inhibitory effect. AC Domain interacts with the C‐terminal segment of FHA with ∼650 nM affinity. ACT does not inhibit biofilm formation by Bordetella lacking the mature C‐terminal domain (MCD), suggesting the direct interaction between AC domain and the MCD is required for the inhibitory effect. Additionally, AC domain disrupts preformed biofilm on abiotic surfaces. The demonstrated inhibition of biofilm formation by a host‐directed protein bacterial toxin represents a novel regulatory mechanism and identifies an unprecedented role for ACT. Abstract : The catalytic domain (AC domain) of Bordetella Adenylate Cyclase Toxin (ACT) interacts with the distal tip of filamentous haemagglutinin, the mature C‐terminal domain with approximately 650 nM affinity. This interaction results in the inhibition of biofilm formation by B. pertussis and B. bronchiseptica in vitro . Despite the AC domain being necessary and sufficient for inhibition, the catalytic activity of ACT is not required for biofilm inhibition.